Reproduction behaviour and stress hormones level in HolsteinFriesian (HF) crossbred cows under various thermolytic measures - NARAYAN, UDAY; SINGH, D V; AHMAD, A H; PATEL, M (The Indian Journal of Animal Reproduction, 2023)
The study, carried out during April - August, 2004, was aimed to find out the effect of summer stress ameliorating,pean measures on reproductive traits and stress hormone levels of HF crossbred cows. Water showering of cows during peak hothours improved their service period (P< 0.05). Other traits, like intensity of estrus signs, number of estrus expressed durings. 6• service period, number of AI per conception, days to attain first post-parturient estrus and length of estrus cycle were foundimproved numerically but statistically non-significant. The stress hormones, like epinephrine and nor-epinephrine werensfer significantly (P< 0.01) lowered as compared to non-showered cows. The study showed that the region experiences markedrates stressful conditions and these can be ameliorated by adopting suitable management measures.
Keywords: HF crossbred; reproduction behaviour; stress hormones; thermolytic measures